Application of O-3/GAC process for advanced and selective removal of natural organic matter from conventionally treated water - Kim, H. C.; Yu, M. J.; Koo, J. Y.; Lee, S. (Drinking Water Treatment, Supply and Management in Asia (IWA-ASPIRE 2005), 2006)
A demonstration plant consisted of ozone/granular activated carbon (GAC) was operated using sand filtered water as an influent to study the feasibility for introduction of an advanced water treatment. In ozonating the sand filtered water, dissolved organic carbon (DOC) slightly increased at an ozone dose of less than 1.0 Mg O-3/mg C, and the largest DOC reduction was exhibited at 1.0 Mg O-3/Mg C. As ozone dosage increased from 1.0 to 5.0 mg O-3/mg C, DOC decreased no more, whereas UV absorbance at 254 nm gradually decreased with increasing ozone dosage. The hydrophobic fraction in natural organic matter (NOM) was considered as a predominant reactant from the result of a rapid decrease in specific ultraviolet absorbance (SUVA). Since the specific reaction sites in the NOM molecule for haloform reaction were attacked by ozonation, the disinfection by-product (DBP) formation potentials could be reduced. The hydrophobic fraction decreased from 36.3% to 28.7% by ozonation and then decreased to 24.2% through carbon adsorption. The hydrophilic fraction changed only by 1.0% during ozonation, while it decreased by 28.3% through carbon adsorption. Therefore, ozonation followed by carbon adsorption is an acceptable process for the reduction of latent risk through selective oxidation and adsorption of different NOM fractions.